THE BASIC PRINCIPLES OF FORECASTING OF AVIATION SYSTEMS OPTIMAL DEVELOPMENT - Linnik, Ivan; Oleg, Mikhail; Bogayskaya, Ekaterina (Proceedings of National Aviation University (archive), 2014)
The article deals with the general mathematical approaches and basic information about the forecasting of modern aircraft systems development. In particular, it considers the dynamic model of determining the optimal characteristics of the aviation system, which are intended for evaluation of reliability and development of the forecasting technology of the aircraft modernization possibility. Dynamic models of optimal development of aviation systems forecasting also allows to evaluate the conditions of these aviation systems’ competitiveness and to be defined with the program for their implementation in the transportation system of a particular state